"A Feminism For the Many": Response to the Comments. (December 2022) - Cobble, Dorothy Sue
Abstract: For the Many: American Feminists and the Global Fight for Democratic Equality recasts American feminism as a global story and reclaims the fight for economic justice and social democracy as a majority tradition of women's politics. This rejoinder by the author of For the Many is the concluding essay in a review dossier on the book. Cobble discusses the book's origins and its contributions to global history, women's history, and political history. She engages with comments and queries from dossier reviewers, a diverse group of historians of Latin America, South Asia, Africa, and Europe. Topics include, among others, the unfinished struggle to revalue care and social reproduction, the influence of India on US feminism, Black internationalism and full-rights feminism, varieties of socialism, rethinking Cold War frameworks, and feminist perspectives on eugenics, race, and sexuality.